Pulmonary embolism due to popliteal vein aneurysm: approach and surgical treatment – a case report. (June 2014) - Maggiore, C; Rizzo, L; Capotondi, C; Dito, R; Taurino, M
Pulmonary embolism is the first presentation in 70–80% in patients with aneurysm of popliteal vein. We present a case of young man admitted in our hospital with respiratory distress, tachycardia and D-dimer >3000 mg/dL. The observation of pulmonary embolism required the placement of a caval temporary filter before the surgical treatment. The use of temporary filter is recommended in symptomatic patients for thromboembolic phenomena, and when ultrasound detects the presence of floating thrombus.